Insular Magnetoencephalography Dipole Clusters in Patients With Refractory Focal Epilepsy. Issue 6 (November 2021) - Chourasia, Nitish; Quach, Michael; Gavvala, Jay
Abstract : Purpose: The clinical significance of magnetoencephalography (MEG) dipole clusters in the insular region in patients with focal epilepsy, when present in conjunction with MEG dipole clusters in other regions of the brain is not known. Methods: All patients (adult and pediatric) with MEG dipole clusters involving the insula were retrospectively evaluated. Patients who underwent any form of surgical intervention were included in the study. Data obtained included age, sex, seizure characteristics, MRI brain, EEG, MEG, intracranial EEG, type of intervention, and seizure outcomes. Results: Twenty-four patients (12 adults and 12 pediatric) were included. Eight patients had one staged intervention and 16 had intracranial evaluation. Ten of 11 patients (91%) with insular coverage by stereotactic EEG had interictal insular spikes, and 5 of 11 patients (45%) had ictal onset from the insula. Combined Engel (I & II) outcomes were seen in five patients with resections/ablations involving the insula MEG dipole clusters as compared with eight patients where the insular MEG dipole clusters were not resected/ablated. Conclusions: Insular MEG dipole clusters identified on surface MEG correlated with interictal spikes in intracranial stereotactic electrode contacts in the insula. The presence of insular MEG dipole clusters, however, does not definitively imply a primary insular onset epilepsy.